2020
DOI: 10.1186/s13000-019-0916-z
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive prostate cancer with somatic loss of the homologous recombination repair gene FANCA: a case report

Abstract: Background: Precision medicine based on genomic analysis of germline or tumor tissue is attracting attention. However, there is no consensus on how to apply the results of genomic analysis to treatment. Case presentation: A 59-year-old man diagnosed with metastatic prostate cancer was diagnosed with castrationresistant prostate cancer. Although he was sequentially treated with enzalutamide and abiraterone, bone metastasis progression was identified by skeletal scintigraphy. Therefore, we sequentially performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…We previously reported genomic analysis of tumor biopsy tissue of prostatic adenocarcinoma cases, which suggested FANCA and BRCA2 loss might be associated with tumor aggressiveness [6,7]. In this case, we investigated genomic feature of intraductal carcinoma of the prostate (IDC-P) and identi ed PTEN pathogenic mutations with LOH.…”
Section: Discussionmentioning
confidence: 97%
“…We previously reported genomic analysis of tumor biopsy tissue of prostatic adenocarcinoma cases, which suggested FANCA and BRCA2 loss might be associated with tumor aggressiveness [6,7]. In this case, we investigated genomic feature of intraductal carcinoma of the prostate (IDC-P) and identi ed PTEN pathogenic mutations with LOH.…”
Section: Discussionmentioning
confidence: 97%
“…Hierarchical clustering analysis showed that the DNA damage repair (DDR) pathways, especially the FA pathway, were deranged across all subtypes of GC (17). The association between FANCA gene variations and breast and ovarian cancers has also been confirmed (18,19), and the other cancers most reported to be associated with FANCA mutations are GC (17), prostate cancer (20) and colorectal cancer (21). There have been no reports on thyroid cancer yet.…”
Section: Discussionmentioning
confidence: 97%
“…Olaparib is a PARP inhibitor that has just been approved for patients with PCa and DDR mutations including BRCA2 loss 8,9 . In the future, PARP inhibitors may be the optimal treatment for PCa with BRCA2 gene alteration in Japan 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…8,9 In the future, PARP inhibitors may be the optimal treatment for PCa with BRCA2 gene alteration in Japan. 10,11 There are various opinions concerning the relationship between BRCA alteration and responsiveness for treatment using ABI or enzalutamide. Annala et al 12 reported that patients with BRCA2 germline mutation exhibited poor responses to therapies that targeted the AR signaling axis, and in contrast, Antonarakis et al 13 reported a good response to AR targeting therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation